METHODS OF CALCULATING METAL REMOVAL UNDER HYDROABRASIVE TREATMENT - Mikhail A. Tamarkin; Andrey A. Tikhonov (Advanced Engineering Research)
Single interaction of an abrasive particle and the work surface under hydroabrasive treatment is considered. Theoretical investigation of the metal removal is carried out. Influence of the flow limit of the detail material, angle of ground particle motion, dynamic pressure of suspension is considered. Functional connections for detecting metal removal for one blow of an abrasive particle and full depth of the particle penetration are derived.